INFLUENCE OF LEADERSHIP STYLE, MOTIVATION, AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE IN PT.DAYANA CIPTA - Turang, Richard Christian (Sam Ratulangi University, 2015)
ABSTRACT In every organization or company, human resource or in this case employee is the main strength. Companyâs goals can be achieved depends on how well the employee performance in it. The purpose of this research is to examine and analyze the influence of leadership style, motivation, and work discipline on employee performance in PT. Dayana Cipta, simultaneously and partially. 86 employees of PT. Dayana Cipta were surveyed as respondents. The sampling technique used is a non probability sampling method and the data testing technique is used within the research includes validity test by factor analysis, reliability test with cronbach. The data analysis in this research is multiple regression analysis using SPSS version 22. The Analysis result shows that leadership style, motivation, and work discipline have a positive influence on employee performance simultaneously. Leadership style influence employee performance partially. Motivation influence employee performance partially. And work discipline influence on employee performance. Keywords: Leadership Style, Motivation, Work Discipline, Employee Performance.